‘Hama dan Musuh Alami’, ‘Obat dan Racun’: Dinamika Pengetahuan Petani Padi dalam Pengendalian Hama - Yunita T. Winarto (Antropologi Indonesia, 1998)
This article presents the author's examination of the dynamic aspects of farmers' knowledge on pest management strategies among rice farmers on the north coast of West Java. In detail, the author takes into account the differences in farmers' reception and learning process in the context of different modes of transmission: 1) the transferral of technology in the Green Revolution programme; and 2) the transmission of knowledge through the Integrated Pest Management Farmers Field Schools. In both settings, metaphor and analogy played a significant role in knowledge acquisition and transmission. Farmers' existing schemes or models of interpretation, or what is called as 'simplified world' of areas of particular experiences dominately underlying farmers' interpretation of the new transmitted ideas and concepts. In the transferral of technology, without the transmission of the related schemes, farmers' interpretations led to undesirable consequences resulting from the misleading and misused metaphors, e.g. 'medicine' for pesticide. On the other hand, knowledge transmission of the integrated pest management not only shifted the existing paradigm of pesticide use, but also enriched farmers' own knowledge through the improved ways of learning in the context of a continuous pest outbreak and economic constraints.